WALL PRESSURE FLUCTUATIONS BEHIND A PIPE NARROWING - Borysyuk, A. O.; Borysyuk, Ya. A. (Science-based technologies, 2017)
Wall pressure fluctuations behind a pipe narrowing of the abrupt, trapezium-like and streamlined axisymmetric shapes are studied experimentally. A sharp increase in their rms level in a finite region immediately downstream of the narrowing, leading up to a pronounced maximum upstream of the point of jet re-attachment, is found. Approximate estimates for the upper limits of the lengths of that region and its typical domains, as well as quantitative relationships both for the distance from the narrowing to the point of maximum rms pressure and for the rms magnitude at this point are obtained for all the shapes. Inspection of the wall pressure power spectrum reveals the presence of a few pronounced low-frequency maxima for all the narrowing shapes. The maxima are found to be associated with the large-scale eddies in the domains of separated and reattached flow, and their frequencies are close to the characteristic frequencies of the eddies’ formation. These maxima are the main distinguishing features of the spectrum under investigation compared to the power spectrum of the wall pressure fluctuations in a fully-developed turbulent flow in a pipe without narrowing. Study of the narrowing shape effects reveals the appropriate changes in the investigated statistical characteristics of the pressure, the power spectrum being more sensitive to the changes in the shape parameters compared to the rms pressure. Recommendations about possible practical application of the obtained results are given.